HIV Risk profile and its socio-demographic correlates among long-distance truckers in West Bengal, India: Evidence from national HIV sentinel surveillance 2017 - Subrata Biswas; Debjit Chakraborty; Piyali Ghosh; Pradeep Kumar; Rajatashuvra Adhikary; Malay Kumar Saha (Wolters Kluwer Medknow Publications, 2020)
Background: Long-distance truckers (LDTs) belong to a special sentinel group with potentially high risk of acquisition of HIV owing to their high mobility, sociodemographic vulnerability, and high-risk behaviors. Objective: The objective is to estimate the prevalence of HIV and identifies its sociodemographic correlates among a representative population of LDTs in West Bengal, India. Methods: Between May and July 2017, HIV Sentinel Surveillance (HSS) was conducted in West Bengal by the National AIDS Control Organization. A total of 749 LDTs were recruited for the study, were interviewed, and tested for HIV. Descriptive and logistic regression analysis of socio-demographics, sexual risk behavior, and HIV serostatus were performed using SAS 9.3.2. Results: The prevalence of HIV among LDT was 1.2% (95% confidence interval [CI] = 0.4-2.0). Mean age was 32.8 years (standard deviation 8.5), 77.1% were currently married, 89.9% were literate, 85.7% visited HSS site for collecting condoms or seeking medical care and treatment, 53.1% were rural residents, 86.7% had sex at least once with a female partner other than wife in the past 6 months, 2.7% had sex with a male partner and 1.7% injected drugs for recreational purpose. Higher age (odds ratio [OR] = 1.1 [95% CI = 1.0-1.1]), literate (OR = 0.3 [95% CI = 0.1-0.9]), visiting HSS sites for collecting condoms or seeking medical care and treatment (adjusted OR [AOR] = 0.2 [95% CI = 0.1-0.6]), rural residence (OR = 0.2 [95% CI = 0.1-0.3]) and duration of stay in home (AOR = 1.3 [95% CI = 1.1-1.5]) were found to be significant predictors of having sex with a female partner other than wife.Conclusion: High HIV burden calls for urgency in the implementation of targeted intervention to minimize HIV risk among LDTs in West Bengal to fight against HIV/AIDS.